Lexical alignment in triadic communication - Foltz, Anouschka; Gaspers, Judith; Thiele, Kristina; Stenneken, Prisca; Cimiano, Philipp (Frontiers in Psychology, 2015)
Lexical alignment refers to the adoption of one’s interlocutor’s lexical items. Accounts of the mechanisms underlying such lexical alignment differ (among other aspects) in the role assigned to addressee-centered behavior. In this study, we used a triadic communicative situation to test which factors may modulate the extent to which participants’ lexical alignment reflects addressee-centered behavior. Pairs of naïve participants played a picture matching game and received information about the order in which pictures were to be matched from a voice over headphones. On critical trials, participants did or did not hear a name for the picture to be matched next over headphones. Importantly, when the voice over headphones provided a name, it did not match the name that the interlocutor had previously used to describe the object. Participants overwhelmingly used the word that the voice over headphones provided. This result points to non-addressee-centered behavior and is discussed in terms of disrupting alignment with the interlocutor as well as in terms of establishing alignment with the voice over headphones. In addition, the type of picture (line drawing vs. tangram shape) independently modulated lexical alignment, such that participants showed more lexical alignment to their interlocutor for (more ambiguous) tangram shapes compared to line drawings. Overall, the results point to a rather large role for non-addressee-centered behavior during lexical alignment.